FENOMENA PROSTITUSI DI PANTAI SAMAS BANTUL YOGYAKARTA - Vivi Ambarwati * (Dimensia: Jurnal Kajian Sosiologi, 2012)
The  phenomenon  of  prostitution  is  usually  often  appear  in  tourist  areas. Prostitution has also appeared in the district of Bantul Samas Beach Yogyakarta despite local laws that prohibit  prostitution. This study aims to: 1). Describe  the  factors that cause  the  existence  of  prostitution  in  Samas  Beach,  2).  Describe  the  community  and local government efforts in dealing with prostitution in Samas Beach.This  study  used  descriptive  qualitative  method  of  analysis.  Informants  in  this study were CSWs (Commercial Sex Workers) Samas Beach, citizens around and Satpol PP  Bantul  regency.  The  research  subject  was  taken  by  snowball  sampling  technique. The  number  of  prostitutes  in  Samas  Beach  is  currently  under  number  10,  so  that sampled quite four informants sex workers because of data and information obtained is adequate. The  process  of  data  collection  is  done  with  the  interview,  non-participatory observation,  field  recording  and  documentation.  Researchers  itself  is  a  qualitative research  instrument,  but  also  coupled  with  the  guidance  interview  and  observation guidelines.  Validity  of  data  using  data  triangulation  technique.  Techniques  in  data analysis  is  the  technique  of  Miles  and  Huberman  interactive  analysis  with  4  stages, namely: data collection, data reduction, data presentation and conclusion.The results showed that: 1). The factors causing the existence of prostitution inSamas Beach is divided into two: internal and external factors. Internal factors causing the existence of prostitution in Samas Beach is derived from the self-sex workers Samas Beach is: do not have other life skills, frustration and trauma and sexual needs. While the  external  factors  causing  the  existence  of  prostitution  in  Samas  Beach  namely: economic factors, call a friend, the narrowness of employment, abuse and misuse of bus terminal facilities stalls shacks wild, 2). Grassroots efforts and local governments in dealing  with  prostitution  in  Samas  Beach  is:  social  control  of  routine  patrolling  and monitoring,  implementing  regulations  Bantul  district  no.  5  year  2007  on  the prohibition of prostitution, conducting raids sex workers, providing skills training, lowcost  health  care  through  mobile  health  center  and  routine  supervision  of  the  police station Sanden and police station Bantul.Key words: the phenomenon of prostitution, sex workers and surrounding communities